Sony CLIÉ for Dummies - Atkin, Denny (Wiley Publishing, 2011)
Shows users how to make the most of Sony's popular Palm OS PDA, the CLIE Sony holds the second largest share of the U.S. PDA market-12.1 percent Guides new and intermediate users through the all the latest CLIE features and functions, from using Graffiti and working with Microsoft Office and PDF files to scheduling appointments, checking e-mail, and beaming data Covers cool multimedia features such as taking digital photos, producing slide shows, recording and watching movies, transferring music, and creating reminders using the built-in voice recorder Written in a friendly, accessible style by PDA guru Denny Atkin, Editorial Director of Handheld Computing magazine